BBS Second Year English Course in TU for the Development of Business Communication Skills - Timalsina, Ramji (Journal of Management, 2021)
Skill for effective communication is an essential quality of a business professional. A course on business communication needs to help them develop such a capacity. The course of English entitled ‘business communication’ prescribed in BBS second year in Tribhuvan University has intended to achieve this goal. On this background, this article analyses how the combination of the contents, language skills and recommended pedagogical approach of tis course is useful to achieve the intended goal of the curriculum. The study is based on Content and Language Integrated Learning (CLIL) principles which argue that language learning should be relevant to the future career of the learners. Only such a course can encourage the learners’ involvement and makes a language class lively and goal oriented. Seen from this perspective, the course under analysis connects the value of English with professional competence with its focus on communication, collaboration, critical thinking, and creativity of its learners. The task based learning pedagogical approach makes both the students and teachers active in the classroom and students continue learning language even beyond the classroom set up. Such a course is useful for career based studies.